How purchasing became a strategic function: from purchasing to external resources management. Issue 2 (13th February 2017) - Poissonnier, Hugues
Abstract : Purpose: This paper aims to show the most important evolutions of the purchasing function. Design/methodology/approach: This paper is a historical approach. Findings: Purchasing is becoming more and more strategic. Research limitations/implications: New skills are required for buyers. Originality/value: This paper aims at explaining the evolution of purchasing which is the most evolving function in companies today. By becoming more and more strategic, purchasing contributes to the evolution of all the company.